Kinerja Dinas Perhubungan Kota Batam dalam Meningkatkan Kualitas Pelayanan Transportasi Umum - Lorena Alfiyani Gultom; Timbul Dompak (Universitas Batanghari Jambi, 2023)
Public transportation is one of the transportation media used by the community together by paying tariffs. Batam City, namely Trans Batam Bus, Metro Trans, non-taxi routes and Ojek. Several public transportation options available to Batam residents depend on the people's purchasing power, so they can choose the mode of transportation that best suits the needs and abilities of the community. Most of the transports that serve passengers are in unfit for operation. The research aims to analyze the performance of the Batam City Transportation Service in improving the quality of public transportation services and to analyze the supporting and inhibiting factors of the Batam City Transportation Service's performance in improving the quality of public transportation services. This research uses a qualitative method with a descriptive approach. The results showed that the performance of the Batam City Transportation Service in improving the quality of public transportation services was good, but not optimal because there were deficiencies in a number of aspects.